1989
DOI: 10.1073/pnas.86.17.6793
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1c receptor is a prominent serotonin receptor subtype in the central nervous system.

Abstract: Neurons in rat central nervous system (CNS) that express 5-HT1c receptor mRNA have been localized by in situ hybridization histochemistry. The 5-HT1c receptor is expressed in a wide variety of cortical and subcortical neurons including hippocampal pyramidal neurons, neurons within most of the central monoaminergic cell groups, neurons in thalamic sensory relay nuclei, and neurons involved in the central processing and regulation of nociceptive transmission.Therefore, the 5-HTic receptor is a prominent but poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(116 citation statements)
references
References 24 publications
(29 reference statements)
6
107
1
1
Order By: Relevance
“…High density is also found in the SNr, globus pallidus and ventro medial thalamus with low amounts detected in many other brain areas [110][111][112]. A widespread distribution of 5-HT 2C receptor mRNA has been demonstrated in rat, monkey and human brains using in situ hybridization techniques [113][114][115][116]. 5-HT 2C receptors are more abundant and more widely expressed in the brain than 5-HT 2A receptors, although there are several areas where both receptors coexist [117].…”
Section: -Ht 2c Receptor Distribution and Cir-cuitry In Cnsmentioning
confidence: 91%
“…High density is also found in the SNr, globus pallidus and ventro medial thalamus with low amounts detected in many other brain areas [110][111][112]. A widespread distribution of 5-HT 2C receptor mRNA has been demonstrated in rat, monkey and human brains using in situ hybridization techniques [113][114][115][116]. 5-HT 2C receptors are more abundant and more widely expressed in the brain than 5-HT 2A receptors, although there are several areas where both receptors coexist [117].…”
Section: -Ht 2c Receptor Distribution and Cir-cuitry In Cnsmentioning
confidence: 91%
“…In-situ hybridization studies have demonstrated that 5-HT2C receptor mRNA is expressed in the VTA (Hoffman and Mezey, 1989;Molineaux et al, 1989;Pompeiano et al, 1994;Wright et al, 1995;Eberle-Wang et al, 1997), both the pars compacta and pars reticulata subdivisions of the SN (Molineaux et al, 1989;Pompeiano et al, 1994;Wright et al, 1995;Eberle-Wang et al, 1997), and in the terminal regions of the nigrostriatal and mesolimbic dopaminergic pathways: the striatum and the NA (Hoffman and Mezey, 1989;Pompeiano et al, 1994;Wright et al, 1995;Eberle-Wang et al, 1997). There is comparatively less evidence for 5-HT2C receptor mRNA in the PFC, however, several studies have shown the presence of 5-HT2C receptor mRNA in the cingulate or anterior cingulate cortex (Hoffman and Mezey, 1989;Pompeiano et al, 1994;Wright et al, 1995).…”
Section: -Ht2c Localizationmentioning
confidence: 99%
“…5-HT2C-Rs are highly expressed in the mPFC and amygdala (Abramowski et al, 1995;Clemett et al, 2000;Li et al, 2003;Lopez-Gimenez et al, 2002;Molineaux et al, 1989;Pompeiano et al, 1994;Sharma et al, 1997;Wright et al, 1995). Pharmacological studies point to a role for this receptor subtype in mediating serotonin's pro-anxiety effects at the level of the amygdala.…”
Section: -Ht2c Receptorsmentioning
confidence: 99%